STUDY OF ELECTROMYOGRAPHY DURING THREE SQUAT EXERCISE PATTERNS AMONG HEALTHY MALES - Phewkham, Natthaphol; Mettamatakul, Ponthakorn; Khemthong, Apiwat; Sukhampha, Suphachai; Prappai, Panupong; Yangjaroen, Supanat; Sridakij, Bunnakon; Thongkumvong, Apiwat; Chumphila, Chaiya; Kongsawat, Supawich; Khunpiban, Nachanon; Chutluang, Panida; et al. (Journal of Sports Science and Health, 2023)
Purpose: The research aimed to study the electromyography during three squat exercise patterns. The objective was to study whether the muscles namely Biceps femoris (BF), Rectus femoris (RF), Vastus medialis (VM), Semitendinosus (SM), and Gastrocnemius (GN) work differently during the three squatting patterns, which were standard squat (STDQ), incline squat (ICQ), and decline squat (DCQ), by using angle adjusting tool. Methods: The 15 healthy male participants’ electromyography of Maximum Voluntary Isometric Contraction (MVIC) by using Isokinetic machine. The participants were asked to randomly perform the three squat patterns for three times according to the metronome rhythm and the lowering pose depth was measured by using goniometer. EMG and MotionTools EMG software was used for the data analysis. Researchers normalized the outcome by comparing the highest MVIC recorded with the electromyography while doing the three squat patterns, then the values were calculated into percentage (%MVIC). The raw data were filtered by using the Butterworth digital filter which was configured the Low pass filter with cutoff frequency at 500 Hertz and High pass filter with cutoff frequency at 20 Hertz; the sampling frequency was configured at 2000 Hertz. The One-Way ANOVA with Repeated Measures was used as part of the statistical analytic method. Results: It was found that each muscle segments worked differently during the three squat patterns and was determined from %MVIC of the muscle segments being studied. The highest electromyography recorded was in VM during DCQ at 113.70±42.09 % and the lowest electromyography recorded was in SM during STQD at 21.02±13.02 %. Moreover, it was found that the electromyography in SM while doing STDQ was lower than ICQ with statistically significant at P<0.05 and the electromyography in RF while doing ICQ was lower than DCQ with statistically significant at P<0.05. Conclusion: The result of this research can be used as a guideline to design the squat exercise patterns specifically for PF and SM; moreover, the result can also have used as a furtherance in designing appropriate exercising equipment to train and build the muscle.